ANALISIS KARAKTERISTIK KANDUNGAN PENCEMAR AIR LIMBAH DAN PROSES PENGOLAHAN AIR MINUM KABUPATEN BADUNG - SOFYAR IRAWAN, AWANG ERRY; Budiarsa Suyasa, I.W.; Suarna, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 1 (2012), 2012)
Installation of water treatment is the required infrastructure in meeting the needs of clean water. During the process of water treatment it produces waste water as a byproduct that could potentially cause pollution if not properly treated. The research purposes of the study are to determine the effectiveness of compliance procedures for waste water treatment, the quality and quantity of waste water and its impact to the environment, as well as providing alternatives for waste water management strategies. Determination of samples were conducted by using purposive sampling method. Samples were taken at two sewer sedimentation and filtration points antl the other four points were taken in the water body and then compared with Governor of Bali Regulation No.8 year 2007. Samples were analywd both in situ and in the laboratory. To determine the effectiveness of the waste water treatment to the conformity assessment procedures, the field conditions were analyzed with a force-field analysis. The effectiveness of waste water management was categorized as moderate. The quality of waste water from the sedimentation basin shows the parameters of TSS (4957.50 mg/I) and Mn (81.68 mg/I), of the tub filtration TSS (665 mg/I) and Mn (12.60 mg/I). The quantity of waste sedimentation basin discharge (Q) o.68 mg/sec, TSS pollutant load (3371.01 mg/sec), Mn (55.51 mg/sec), filtration basin discharge (Q) o.68 mg/sec, load TSS pollutant (332.50 mg/sec), Mn (6.30 mg/sec). Based on the force-field analysis conducted, some alternative strategies were proposed such as building facilities for waste management, environmental m.inagement implementation based on the appropriate planning, implementation of waste water disposal permit including fulfill the technical conditions as required, technical capacity building of human resources, and land use.
Keywords: quality, quantity, effectiveness, waste water management